Evaluation of MAC's distributed queuing algorithm for Internet of things applications - Agel, Mabruka Mohamed; Habaebi, Mohamed Hadi; Alnahdi, Sameha; Islam, Md. Rafiqul (2017)
Internet of Things and Machine-to-Machine communications have contributed significantly on our daily life. Nevertheless, from the networking aspect they introduced a huge challenge for the performance and quality of services of networks. In this paper, a Distributed Queuing Access for LTE protocol was analysed to enhance the random access performance for Machine to machine (M2M) applications. The M2M communications presented countless solicitations that can over-burden the access channel of the present LTE network. This prompts to an expansion in the collision probability and results in a noteworthy access delay. The introduced protocol does improve the performance of Medium access layer in terms of blocking probability, access delay, energy utilization and number of re-transmissions attempts in comparison with the standard LTE protocol without altering the existing LTE outline structure. The new protocol is intended to ensure that the random access procedure of the ordinary UE gadget will not be affected bringing about consistent implementation for the proposed convention.